Forecasting of wind energy technology domains based on the technology life cycle approach - Mohammad Dehghani Madvar; Farzin Ahmadi; Reza Shirmohammadi; Alireza Aslani (Energy Reports, 2019)
Wind energy technologies are being developed in order to reduce the costs of the generated electricity and increasing technological performance. Therefore, understanding the technological development paths is an important part of the debates among technology developers and policymakers of energy systems. Due to recognize the wind technology orientation, the published patents in wind technology have been analyzed. Five groups of technology have been found, and the result of technological trends and life cycles for each one has been discussed. In order to clarify the main issues in each technology domain, a cluster dendrogram of frequent keywords in each domain through text analysis has been drawn. Text analysis of all published patents illustrated that controlling pitch and larger blade design are the most frequent words in the "blades and rotor" and "control of turbines" domains respectively. Two main domains of technology have been considered a lot in patents, "blades and rotor" and "control of turbines". In the next step, the technological life cycles of all five domains have been discussed. In spite of the number of published patents in "blades and rotor" and "control of turbines" domains, "nacelle" is in the maturity stage.
Keywords: 330; Patent analysis; Technological life cycle; Technology orientation; Text analysis; Wind energy